Effect Of Calcium Channel Blocker With Other Antihypertensive Agents On Lower Urinary Tract Symptoms And Its Impact On Patients’ Quality Of Life - Salman, Muhammad (2018)
Lower urinary tract symptoms (LUTS) include all urological symptoms related to voiding, storage and post-micturition, which are associated with great emotional distress to sufferers and high economic burden to the society. The development of LUTS is deemed to be associated with certain medications and diseases. Among the former, calcium channel blockers (CCBs) are believed to be involved in development or worsening of LUTS, however, information concerning such correlation is sparse. Therefore, the present study was designed to investigate the effects of CCBs on LUTS and its impact on patients‘ sleep pattern, depression and quality of life (QOL). This study was carried out in 2 phases; Phase-I included a psychometric validation study wherein the International Prostate Symptom Score-Urdu (IPSS-Urdu) was developed and validated, whereas Phase-II was a cross-sectional study to evaluate the effect of CCB mono- and combined-therapy on LUTS. IPSS-Urdu was developed by a two-step forward and back translation, and evaluated for its psychometric properties in a prospective study involving patients (n = 267) suffering from LUTS, conducted at the Outpatient Urology Department, Mayo Hospital, Lahore, Pakistan. Overall reliability of IPSS-Urdu was satisfactory [Cronbach‘s alpha = 0.72, Intra-Class Correlation Coefficient (ICC) of symptom-questions = 0.92 and ICC of QOL index = 0.75]. Exploratory factor analysis revealed that two factors were consistent, which together explained 59.8% of the variance. Confirmatory factor analysis further showed two-factor model, with acceptable fitting patterns.